2010
DOI: 10.1016/j.molcel.2010.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Phases of siRNA Synthesis in an Endogenous RNAi Pathway in C. elegans Soma

Abstract: SUMMARY Endogenous RNA-directed RNA polymerases (RdRPs) are cellular components capable of synthesizing new complementary RNAs from existing RNA templates. We present evidence for successive engagement of two different RdRPs in an endogenous siRNA-based mechanism targeting specific mRNAs in C. elegans soma. In the initiation stage of this process, a group of mRNA species are chosen as targets for downregulation, leading to accumulation of rare 26-nt 5′-phosphorylated antisense RNAs that depend on the RdRP homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
249
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(265 citation statements)
references
References 59 publications
10
249
0
1
Order By: Relevance
“…S7B; Supplemental Table S7) (sequence data were obtained from GEO, accession: GSE20649) (Corrêa et al 2010). A similar reduction of miRNA star level in rde-1 mutants was also observed in another library obtained from the GEO, GSE19414 (Gent et al 2010) (data not shown). These results suggest that the star miRNA strands are preferentially sorted into or stabilized in RDE-1 Argonaute protein in C. elegans.…”
Section: Resultssupporting
confidence: 61%
“…S7B; Supplemental Table S7) (sequence data were obtained from GEO, accession: GSE20649) (Corrêa et al 2010). A similar reduction of miRNA star level in rde-1 mutants was also observed in another library obtained from the GEO, GSE19414 (Gent et al 2010) (data not shown). These results suggest that the star miRNA strands are preferentially sorted into or stabilized in RDE-1 Argonaute protein in C. elegans.…”
Section: Resultssupporting
confidence: 61%
“…There are four RdRPs in C. elegans: RRF-3 functions in the production of 26G siRNAs (Gent et al 2010), EGO-1 and RRF-1 have partially overlapping roles in 22G siRNA formation ), and RRF-2, which is closely related to RRF-1, has an unknown role (Sijen et al 2001). From a phylogenetic analysis of nematode RdRPs, we identified likely orthologs of the three RdRP subfamilies, RRF-1, RRF-3, and EGO-1 in each of the other three nematode species (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These biases could reflect the sequence motifs preferred by RdRPs on mRNA templates for the synthesis of 22G RNAs. Whereas considering all 22-nt RNAs together suggested a modest preference for a C or U immediately upstream of 22-nt RNAs (Gent et al 2010), examining RNAs with different 5 ′ nucleotides separately clarifies the observation and reveals that synthesis of RNAs with 5 ′ nucleotides other than G appear to be promoted by specific upstream bases on mRNA templates.…”
Section: G Rnas and Their Derivatives Are Made From Characteristic mentioning
confidence: 92%